2019
DOI: 10.1104/pp.19.00384
|View full text |Cite
|
Sign up to set email alerts
|

A Neighboring Aromatic-Aromatic Amino Acid Combination Governs Activity Divergence between Tomato Phytoene Synthases

Abstract: Carotenoids exert multifaceted roles to plants and are critically important to humans. Phytoene synthase (PSY) is a major ratelimiting enzyme in the carotenoid biosynthetic pathway. PSY in plants is normally found as a small enzyme family with up to three members. However, knowledge of PSY isoforms in relation to their respective enzyme activities and amino acid residues that are important for PSY activity is limited. In this study, we focused on two tomato (Solanum lycopersicum) PSY isoforms, PSY1 and PSY2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 76 publications
(128 reference statements)
3
50
0
Order By: Relevance
“…The lycopene produced in E. coli can be quantified photometrically, which provides a convenient read-out corresponding to PSY enzymatic activity as phytoene is readily and fully converted by CrtI (Camagna et al, 2019). This system was successfully used to determine PSY activity differences caused by single nucleotide or amino acid polymorphisms (Welsch et al, 2010;Mlalazi et al, 2012;Cao et al, 2019).…”
Section: Analysis Of Boor-psy Interaction In a Heterologous Bacterialmentioning
confidence: 99%
See 1 more Smart Citation
“…The lycopene produced in E. coli can be quantified photometrically, which provides a convenient read-out corresponding to PSY enzymatic activity as phytoene is readily and fully converted by CrtI (Camagna et al, 2019). This system was successfully used to determine PSY activity differences caused by single nucleotide or amino acid polymorphisms (Welsch et al, 2010;Mlalazi et al, 2012;Cao et al, 2019).…”
Section: Analysis Of Boor-psy Interaction In a Heterologous Bacterialmentioning
confidence: 99%
“…PSY was also shown to interact with the upstream substrate-delivering enzyme GGPP synthase (GGPS) and acts as a constituent of metabolons containing up-and downstream enzymes to provide an additional possibility for regulation at the level of protein-protein interaction (Maudinas et al, 1977;Fraser et al, 2000;Ruiz-Sola et al, 2016;Camagna et al, 2019). Its evolutionary conserved features for activity across various organisms were recently analyzed (Cao et al, 2019). As PSY protein level is crucial for overall pathway activity and carotenoid amounts, a tight control of PSY proteostasis is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Activity studies and site directed mutagenesis confirmed the role of this structural element [187]. Additional amino acid differences were found to be responsible for large differences in the activities of the daffodil and maize PSY enzymes, used to engineer "Golden rice" plants with different provitamin A contents [187,188]. The identification of highly-efficient PSY alleles paves the way for generating them in other tissues or plant species by employing modern gene editing tools, such as CRISPR mediated targeted base editing [189].…”
Section: Regulation Of Carotenogenesismentioning
confidence: 84%
“…In cassava, the allelic variation (Ala > Asp mutation) in PSY leads to enhanced enzymatic activity and, hence, to increased carotenoid accumulation in yellow-rooted cassava varieties with increased provitamin A content [186]. Recently, examination of two tomato PSY isoforms (PSY1 and PSY2) identified a neighboring aromatic-aromatic combination in their core structure, which is conserved in PSY enzymes from different species but absent in the fruit specific and enzymatically less efficient PSY1 [187]. Activity studies and site directed mutagenesis confirmed the role of this structural element [187].…”
Section: Regulation Of Carotenogenesismentioning
confidence: 99%
See 1 more Smart Citation